Hemodynamic modeling of long‐term aspirin effects on blood oxygenated level dependent responses at 7 Tesla in patients at cardiovascular risk. (23rd September 2020) - Do, Cao‐Tri; Manjaly, Zina‐Mary; Heinzle, Jakob; Schöbi, Dario; Kasper, Lars; Pruessmann, Klaas P.; Stephan, Klaas Enno; Frässle, Stefan
Abstract: Aspirin is considered a potential confound for functional magnetic resonance imaging (fMRI) studies. This is because aspirin affects the synthesis of prostaglandin, a vasoactive mediator centrally involved in neurovascular coupling, a process underlying blood oxygenated level dependent (BOLD) responses. Aspirin‐induced changes in BOLD signal are a potential confound for fMRI studies of at‐risk individuals or patients (e.g. with cardiovascular conditions or stroke) who receive low‐dose aspirin prophylactically and are compared to healthy controls without aspirin. To examine the severity of this potential confound, we combined high field (7 Tesla) MRI during a simple hand movement task with a biophysically informed hemodynamic model. We compared elderly individuals receiving aspirin for primary or secondary prophylactic purposes versus age‐matched volunteers without aspirin medication, testing for putative differences in BOLD responses. Specifically, we fitted hemodynamic models to BOLD responses from 14 regions activated by the task and examined whether model parameter estimates were significantly altered by aspirin. While our analyses indicate that hemodynamics differed across regions, consistent with the known regional variability of BOLD responses, we neither found a significant main effect of aspirin (i.e., an average effect across brain regions) nor an expected drug × region interaction. While our sample size is not sufficiently large to rule out small‐to‐medium global effects of aspirin, we had adequate statistical power for detecting the expected interaction. Altogether, our analysis suggests that patients with cardiovascular risk receiving low‐dose aspirin for primary or secondary prophylactic purposes do not show strongly altered BOLD signals when compared to healthy controls without aspirin. Abstract : Aspirin‐induced changes in blood oxygenated level dependent (BOLD) signal are a potential confound for fMRI studies of at‐risk individuals or patients (e.g. with cardiovascular conditions or stroke) who receive low‐dose aspirin prophylactically and are compared to healthy controls without aspirin. To examine the severity of this potential confound, we combined high field MRI with a biophysically informed hemodynamic model, testing for differences in BOLD responses between these two groups.